Price Pressure in the Government Bond Market - Greenwood, Robin; Vayanos, Dimitri (American Economic Review, 2010)
What determines the term structure of interest rates? Standard economic theory links the interest rate for maturity T to the willingness of a representative agent to substitute consumption between times 0 and T. The standard model contrasts sharply with a more informal view based on investors ’ preferred habitat, proposed by John Culbertson (1957) and Franco Modigliani and Richard Sutch (1966). According to the preferred-habitat view, there are investor clienteles with preferences for specific maturities, and the interest rate for a given maturity is influenced by the demand of the corresponding clientele and the supply of bonds with that maturity. For example, the typical clientele for long-term bonds are pension funds. An increase in their demand would be expected to raise prices of long-term bonds and thus lower long-term interest rates. In short, preferred habitat implies that there is price pressure in the bond market. While the preferred-habitat view has intuitive appeal, it has not entered into the academic mainstream, typically being relegated to a paragraph in MBA-level textbooks. One reason for this is the mixed findings in early empirical studies of the term structure. Specifically, between 1962 and 1964, the US Treasury and Federal Reserve raised the supply of short-term government debt while simultaneously lowering the supply of long-term debt. This program, known as Operation Twist, aimed to raise short-term interest rates, and so improve the balance of payments, while also lowering long-term rates to stimulate private investment. A number of papers evaluated Operation Twist, and while they reached different conclusions, none found